2000
DOI: 10.1161/01.hyp.35.4.898
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Hypertension, Microalbuminuria, and Risk of Ischemic Heart Disease

Abstract: Abstract-Albumin excretion in urine is positively correlated with the presence of ischemic heart disease and atherosclerotic risk factors. We studied prospectively whether a slight increase of urinary albumin excretion, ie, microalbuminuria, adds to the increased risk of ischemic heart disease among hypertensive subjects. In 1983 and 1984, blood pressure, urinary albumin/creatinine concentration ratio, plasma total and HDL cholesterol levels, body mass index, and smoking status were obtained in a population-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
243
0
18

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 388 publications
(267 citation statements)
references
References 58 publications
6
243
0
18
Order By: Relevance
“…1,2,4-6 Accordingly, it was recently established that microalbuminuria confers a fourfold increased risk of ischaemic heart disease among hypertensive or bordeline hypertensive subjects. 1 The described association of increased UAE with LV hypertrophy 6,8 may explain some of the prognostic significance of microalbuminuria. Indeed, in our study, higher indexed LV mass was found in microalbuminuric subjects than in normoalbuminuric individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2,4-6 Accordingly, it was recently established that microalbuminuria confers a fourfold increased risk of ischaemic heart disease among hypertensive or bordeline hypertensive subjects. 1 The described association of increased UAE with LV hypertrophy 6,8 may explain some of the prognostic significance of microalbuminuria. Indeed, in our study, higher indexed LV mass was found in microalbuminuric subjects than in normoalbuminuric individuals.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Indeed, it is well established that microalbuminuria can be considered predictive of the development of overt proteinuria and of cardiovascular mortality in diabetic patients. 3 The same adverse prognostic conclusion seems to emerge from recent research in tively correlated to LVMI (r = 0.46, P Ͻ 0.001) and relative wall thickness (r = 0.47, P Ͻ 0.001).…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The pathophysiological mechanisms underlying this association have not yet been fully elucidated, although they likely involve a number of different factors. In fact, it has been shown that a moderate reduction in glomerular filtration rate is associated with a cluster of haemodynamic and proatherogenic abnormalities, such as increased blood pressure (BP) load, insulin resistance, dyslipidaemia, hyperhomocysteinaemia, endothelial dysfunction, and systemic inflammation, which, in turn, may concur to foster the development of cardiac and vascular complications.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Recently, it was proven to be a predictor of cardiovascular morbidity and mortality in long term longitudinal studies. 5,6 Even though the pathogenesis of increased urinary albumin excretion (UAE) is at present still unclear, this abnormality has been proposed as a useful integrated marker of target organ damage (TOD) and increased cardiovascular risk. 7 However, routine evaluation of Mi is not recommended by international guidelines as part of the diagnostic work-up of every hypertensive patient and its potential diagnostic power has not yet been fully exploited in clinical practice.…”
Section: Introductionmentioning
confidence: 99%